(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In today’s rapidly developing world, the integration of technology and entrepreneurship is becoming increasingly important for economic growth and innovation. As the global landscape continues to shift toward a knowledge-based economy, equipping young people with the skills and mindsets necessary to thrive in entrepreneurship is critical. This article explores the importance of guiding youth in creative entrepreneurship education through hands-on technology training. By combining technical skills with an entrepreneurial mindset, we can empower the next generation of innovators, problem solvers and job creators.